the hardy boys mystery stories 10 : what happened at midnight - Dixon, Franklin W. (Canada Grosset & Dunlap, 1931)
Frank and Joe Hardy receive an unusual assignment from their detective father. They are to break into the house of a Bayport neighbor, Malcolm Wright, and retrieve a top-secret invention that the scientist had hidden in his study before leaving for California. The invention is in danger of being stolen, and the boys race against time to beat the thieves at their own game.
English